The Structural Interface between HIV-1 Vif and Human APOBEC3H - Ooms, Marcel; Letko, Michael; Simon, Viviana (Journal of virology, 2017)
Human APOBEC3H (A3H) is a cytidine deaminase that inhibits HIV-1 replication. To evade this restriction, the HIV-1 Vif protein binds A3H and mediates its proteasomal degradation. To date, little information on the Vif-A3H interface has been available. To decipher how both proteins interact, we first mapped the Vif-binding site on A3H by functionally testing a large set of A3H mutants in single-cycle infectivity and replication assays. Our data show that the two A3H α-helixes α3 and α4 represent the Vif-binding site of A3H. We next used viral adaptation and a set of Vif mutants to identify novel, reciprocal Vif variants that rescued viral infectivity in the presence of two Vif-resistant A3H mutants. These A3H-Vif interaction points were used to generate the first A3H-Vif structure model, which revealed that the A3H helixes α3 and α4 interact with the Vif β-sheet (β2-β5). This model is in good agreement with previously reported Vif and A3H amino acids important for interaction. Based on the predicted A3H-Vif interface, we tested additional points of contact, which validated our model. Moreover, these experiments showed that the A3H and A3G binding sites on HIV-1 Vif are largely distinct, with both host proteins interacting with Vif β-strand 2. Taken together, this virus-host interface model explains previously reported data and will help to identify novel drug targets to combat HIV-1 infection. IMPORTANCE HIV-1 needs to overcome several intracellular restriction factors in order to replicate efficiently. The human APOBEC3 locus encodes seven proteins, of which A3D, A3F, A3G, and A3H restrict HIV-1. HIV encodes the Vif protein, which binds to the APOBEC3 proteins and leads to their proteasomal degradation. No HIV-1 Vif-APOBEC3 costructure exists to date despite extensive research. We and others previously generated HIV-1 Vif costructure models with A3G and A3F by mapping specific contact points between both proteins. Here, we applied a similar approach to HIV-1 Vif and A3H and successfully generated a Vif-A3H interaction model. Importantly, we find that the HIV-1 Vif-A3H interface is distinct from the Vif-A3G and Vif-A3F interfaces, with a small Vif region being important for recognition of both A3G and A3H. Our Vif-A3H structure model informs on how both proteins interact and could guide toward approaches to block the Vif-A3H interface to target HIV replication.